Rise of the planet of the apes [videorecording (DVD)] - Wyatt, Rupert, 1972-; Lithgow, John, 1945-; Cox, Brian, 1946-; Franco, James, 1978-; Pinto, Freida, 1984-; Felton, Tom, 1987-; Oyelowo, David; Serkis, Andy (20th Century Fox Home Entertainment, 2011)
During experiments to find a cure for Alzheimer's disease, a genetically-enhanced chimpanzee uses its greater intelligence to lead other apes to freedom.